Kualitas Biskuit Kombinasi Tepung Uwi Ungu (Dioscorea alata) dan Tempe Kacang Merah (Phaseolus vulgaris L.) - br Sinuraya, Theresia U; Pranata, Franciscus S; Swasti, Yuliana R (AGRITEKNO: Jurnal Teknologi Pertanian, 2024)
Biscuits are a popular snack among people of all ages. The combination of purple yam flour (Dioscorea alata L.) and red bean tempeh flour (Phaseolus vulgaris L.) as a substitute for wheat flour is expected to increase the nutritional value of biscuits. The purpose of this study was to determine the effect of the combination of purple yam and red bean tempeh flour on the quality of biscuits through chemical, physical, and microbiological analyses and to compare the quality of biscuits produced using combinations of purple yam flour and red bean tempeh. This study employed a Completely Randomized Design with four flour combinations: the control (100% wheat flour), treatment A (60% wheat flour:20% purple yam flour:20% red bean tempeh flour), treatment B (60% wheat flour:25% purple yam flour:15% red bean tempeh flour), and treatment C (60% wheat flour:30% purple yam flour:10% red bean tempeh flour). The results showed that purple yam flour and red bean tempe flour affect the ash, protein, lipid, insoluble fiber, soluble fiber, and fracturability of biscuits. The best biscuit based on chemical, physical, and microbiological analyses was produced using the combination of 60% wheat flour:20% purple yam flour:20% red bean tempeh flour.